When to Return for Usual Activity After ACS The Benefit of Cardiac Rehabilitation - Cholid Tri Tjahjono (Universitas Brawijaya, 2020)
Cardiac rehabilitation (CR) can be managed as global long-term care and comprehensive risk reduction of cardiac patients based on preventive care through a professional multi-disciplinary integrated process approach.11 Multidisciplinary CR elements include: patient evaluations, physical activity counselling, exercise training, diet/nutritional counseling, psychosocial management, lipid management, smoking avoidance, management of weight, and regulation of blood pressure. Exercise training if begun at the post-ACS acute phase, would achieve its greatest beneficial effect on the process of LV remodeling in the dysfunctional LV and cardiopulmonary rehabilitation in patients after acute coronary syndrome. Cardiac rehabilitation (CR) can be managed as global long-term care and comprehensive risk reduction of cardiac patients based on preventive care through a professional multi-disciplinary integrated process approach